THE PRINCIPLE OF COMPENSATION AS A GUARANTEE OF HUMAN RIGHTS AND FREEDOMS: (AS EXEMPLIFIED BY THE LEGISLATION OF THE RUSSIAN FEDERATION) - Andreevich Demichev, Alexey; Aleksanovich Engibaryan, Manvel; Aleksanovna Iliukhina, Vera; Vasilevich Paramonov, Aleksandr (Gênero & Direito, 2020)
The article aims at analyzing the principle of compensation enshrined in the Russian legislation as a guarantee of human rights and freedoms. Moreover, the authors of the article proceed from the positivist understanding of law principles. The main scientific method is formal legal analysis or interpretation of international and Russian laws on compensation. Based on different reasons, the authors have developed six classifications of compensation. The article concludes that 1) the principle of compensation is an interdisciplinary principle of the Russian law; 2) the principle of compensation is among effective guarantees of human rights and freedoms in Russia, while the implementation of rules governing this institute contributes to the restoration of social justice in different spheres of social life; 3) compensation covers material and non-material damage caused to individuals and legal entities, as well as costs or expenses that arise in cases specified in the relevant regulatory acts; 4) the actual grounds for compensation payments can only be lawful and unlawful action or inaction, as well as events and conditions enshrined in the corresponding law. As a result, the following definition of compensation has been proposed: compensation is reimbursement to individuals and legal entities of material and non-material damage or expenses caused by lawful and unlawful action (inaction), events and conditions, which aims at restoring social justice in cases established by regulatory legal acts.